Economia solidária e finanças de proximidade: Realidade social e principais características dos empreendimentos de finanças solidárias no Brasil - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This text aims to analyze the data of "solidarity finance" enterprises that make up the Information System of Solidarity Economy (Sies). The most common types of projects featured in this category are: community bank, credit cooperative and revolving fund. Each has different origing and operational structure. Such experiments are generally created in order to provide lines and credit channels more streamlined, taking into account the characteristics of this type of socioeconomic organization and enable viable alternatives to the official credit system and market. As in all branches of manifestation of solidarity economy, among solidarity finance enterprises there are also different examples of successful actions, as well as structural factors of precariousness.
Keywords: J54; Z13; 330; solidarity economy; developments of solidarity finance; collective organization; local development; self-management